A polyvinyl chloride composition and use thereof

CN122958799APending Publication Date: 2026-10-23CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510491066.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但是PVC与纤维之间的界面作用较弱,进而影响其耐高温蠕变的效果改善以及力学等机械性能

Benefits of technology

[0006]为克服上述现有技术的至少一种缺陷,第一方面,本发明的一种实施方式提供了一种聚氯乙烯组合物,包括聚氯乙烯和添加剂,所述添加剂包括改性的玻璃纤维;其中,所述改性的玻璃纤维是通过将叔胺基硅烷偶联剂与玻璃纤维反应制得。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958799A_ABST
    Figure CN122958799A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of polyvinyl chloride composition and its application, the polyvinyl chloride composition includes polyvinyl chloride and additive, the additive includes modified glass fiber;Wherein, the modified glass fiber is by reacting tertiary amine group silane coupling agent with glass fiber and is prepared.The polyvinyl chloride composition of an embodiment of the present application can be used as the preparation of polyvinyl chloride material, and the prepared polyvinyl chloride material has higher high-temperature creep resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to polyvinyl chloride (PVC), and more particularly to a PVC material with high-temperature creep resistance. Background Technology

[0002] In coal mining, belt conveyors are crucial equipment for coal transportation, primarily composed of idlers and belts. Currently, most belt conveyor idlers are metal, which are widely used due to their mature technology and low cost. However, metal idlers are heavy and have poor corrosion resistance, leading to high energy consumption during operation. Furthermore, with the increasing application and development of mining products, lightweight mining idlers have become an important development direction. Therefore, developing polymer-based idler material technology (lightweight, corrosion-resistant, and easy to install) for the processing and manufacturing of non-metallic idlers to replace metal idlers has become one of the main research and development directions for idlers.

[0003] For polymer materials used in coal mines, given the actual requirements of the coal mining environment (such as the flammability and explosiveness of coalbed methane and other associated gases), key technical indicators for mining polymer materials typically include flame retardancy and antistatic properties. However, for most plastics and other polymer materials, due to their high insulation properties, they easily generate and accumulate static charges, leading to electrostatic hazards, such as potential fires or explosions. Therefore, flame retardancy and antistatic properties become crucial technical indicators for mining polymer materials.

[0004] Furthermore, during idler roller operation, friction between components can cause the roller temperature to reach 50°C or higher. In certain scenarios (such as outdoors or at midday in summer), the actual temperature of the idler roller can be even higher. For idler rollers made of polymer materials, the polymer material (such as PVC) typically softens upon heating, especially in high-load applications. Therefore, when polymer material idler rollers operate continuously in the high-temperature environment of special coal mining scenarios (open-pit mines in summer, at midday, or outdoors), they may experience creep deformation due to heavy loads and the continuous temperature rise caused by continuous operation.

[0005] To improve the high-temperature deformation resistance (high-temperature creep) and other properties of polymer materials (such as PVC), existing technologies typically employ nanoparticles or fibers to fill and modify the polymer matrix. However, the interfacial bonding between spherical nanoparticles and fibers and the resin matrix is ​​usually poor. Furthermore, spherical nanoparticles have a smaller impact on the high-temperature creep resistance of polymers than fiber-reinforced polymers. Therefore, using fibers as reinforcing materials is more effective in improving the high-temperature creep resistance of PVC. However, the interfacial interaction between PVC and fibers is weak, which in turn affects the improvement in high-temperature creep resistance and mechanical properties. Summary of the Invention

[0006] To overcome at least one of the defects of the prior art, in a first aspect, one embodiment of the present invention provides a polyvinyl chloride composition comprising polyvinyl chloride and an additive, wherein the additive comprises modified glass fiber; wherein the modified glass fiber is prepared by reacting a tertiary amine silane coupling agent with the glass fiber.

[0007] Secondly, one embodiment of the present invention provides a polyvinyl chloride material, which is obtained by extruding the components of the above-mentioned polyvinyl chloride composition after mixing them.

[0008] Thirdly, one embodiment of the present invention provides an idler roller, including a roller body comprising the aforementioned polyvinyl chloride material.

[0009] Fourthly, one embodiment of the present invention provides a modified glass fiber prepared by reacting a tertiary amine silane coupling agent with the glass fiber.

[0010] Fifthly, one embodiment of the present invention provides the use of the above-described polyvinyl chloride composition, the above-described polyvinyl chloride material, or the above-described modified glass fiber in the preparation of idler roller bodies.

[0011] The polyvinyl chloride composition of one embodiment of the present invention can be used to prepare polyvinyl chloride materials, and the resulting polyvinyl chloride materials have high resistance to high temperature creep. Attached Figure Description

[0012] The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of the invention. Wherein:

[0013] Figure 1 These are high-temperature creep test diagrams of the polyvinyl chloride materials prepared in Examples 1 and 2 and Comparative Examples 1 to 3 of the present invention. Detailed Implementation

[0014] Typical embodiments embodying the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various variations in different embodiments without departing from the scope of the present invention, and the description herein is for illustrative purposes only and not intended to limit the present invention.

[0015] One embodiment of the present invention provides a modified glass fiber (m-GF) prepared by reacting a tertiary amine silane coupling agent with glass fiber.

[0016] In one embodiment, the tertiary amine silane coupling agent comprises one or more of the following compounds:

[0017]

[0018] R1, R2, R4, and R5 are each independently selected from alkyl groups containing 1 to 3 carbon atoms; R3 is selected from alkyl groups or alkoxy groups containing 1 to 3 carbon atoms.

[0019] a and b can be 1, 2, 3 or 4 independently.

[0020] In one embodiment, R1, R2, R4, and R5 in the tertiary aminosilane coupling agent are each independently methyl or ethyl.

[0021] In one embodiment, R3 is methyl, ethyl, methoxy, or ethoxy.

[0022] In one implementation, a is 2 or 3, and b is 2 or 3.

[0023] In one embodiment, the tertiary aminosilane coupling agent may be 3-piperazinylpropylmethyldimethoxysilane (CAS: 128996-12-3), 3-piperazinylpropyltrimethoxysilane (CAS: 40762-28-5), N-(piperazinylethyl)-3-aminopropylmethyldimethoxysilane (CAS: 128644-51-9), N-(piperazinylethyl)-3-aminopropyltrimethoxysilane, N-(3-dimethylethyl)-3-aminopropylmethyldimethoxysilane (CAS: 94491-23-3), N-(3-dimethylethyl)-3 -One or more of the following: N-dimethylaminopropyl-aminopropylmethyldimethoxysilane (HD-121), N-dimethylaminopropyl-aminopropyltrimethoxysilane, N-(2-dimethylaminoethyl)-3-aminopropylmethyldimethoxysilane (CAS: 224638-27-1), N-(2-dimethylaminoethyl)-3-aminopropyltrimethoxysilane, N,N-diethyl-3-aminopropyltrimethoxysilane (CAS: 41051-80-3), and N,N-dimethyl-3-aminopropyltrimethoxysilane (CAS: 2530-86-1).

[0024] In one embodiment, the glass fiber can be a short glass fiber with a diameter of 5-20 μm and a length of 4-40 mm. For example, the diameter of the glass fiber can be 6 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or 18 μm, and the length can be 4.5 mm, 5 mm, 6 mm, 8 mm, 10 mm, 12 mm, 13 mm, 14 mm, 15 mm, 20 mm, 25 mm, 30 mm or 35 mm.

[0025] In one embodiment, in the preparation of modified glass fiber, the mass ratio of glass fiber to tertiary amine silane coupling agent is 100:0.2 to 10, for example 100:0.5, 100:0.8, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:8.

[0026] One embodiment of the present invention provides a method for preparing the above-mentioned modified glass fiber, comprising: hydrolyzing a tertiary amine silane coupling agent under conditions of pH 2 to 6 (e.g., 3, 4, or 5), followed by adding glass fiber to carry out the reaction. Further, both the hydrolysis reaction and the reaction after adding glass fiber are carried out at 30 to 70°C, for example, the reaction temperature can be 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, or 65°C.

[0027] In one embodiment, the hydrolysis reaction time of the tertiary aminosilane coupling agent can be 0.2 to 2 hours, for example, 0.5 hours, 0.8 hours, 1 hour, 1.2 hours, 1.5 hours or 1.8 hours.

[0028] In one embodiment, the reaction time after adding glass fiber in the preparation of modified glass fiber can be 0.2 to 2 hours, for example 0.5 hours, 0.8 hours, 1 hour, 1.2 hours, 1.5 hours or 1.8 hours.

[0029] In one embodiment, the method for preparing modified glass fiber includes: dissolving a tertiary amine silane coupling agent in a solvent, adjusting the pH of the solution to 2-6 using an acidic adjusting agent, carrying out a hydrolysis reaction at 30-70°C for 0.2-2 hours, then adding glass fiber, and continuing the reaction at 30-70°C for 0.2-2 hours.

[0030] One embodiment of the present invention provides a polyvinyl chloride composition comprising polyvinyl chloride (PVC) and additives, the additives including the above-described modified glass fibers.

[0031] In one embodiment, a polyvinyl chloride material with a reversible cross-linked network can be formed by blending polyvinyl chloride with modified glass fiber. The presence of the cross-linked network gives the polyvinyl chloride material better high-temperature creep resistance.

[0032] In one embodiment, the mass ratio of polyvinyl chloride to modified glass fiber is 100:5 to 40, for example, 100:10, 100:15, 100:20, 100:25, 100:30 or 100:35.

[0033] In one embodiment, the polyvinyl chloride composition additives include one or more of antistatic agents (e.g., long-lasting antistatic agents), toughening agents, stabilizers, and processing flow aids.

[0034] In one embodiment, the polyvinyl chloride composition includes 100 parts by weight of polyvinyl chloride, 5 to 40 parts by weight (e.g., 10, 15, 20, 25, 30, or 35 parts by weight) of modified glass fiber, 2 to 15 parts by weight of antistatic agent (e.g., 3, 4, 5, 6, 8, 10, or 12 parts by weight), 5 to 30 parts by weight (e.g., 10, 15, 20, or 25 parts by weight) of toughening agent, 2 to 10 parts by weight (e.g., 4, 5, 6, or 8 parts by weight) of stabilizer, and 0.5 to 4 parts by weight (e.g., 1, 2, or 3 parts by weight) of processing flow aid.

[0035] In one embodiment, the polyvinyl chloride composition comprises 100 parts by weight of polyvinyl chloride, 10 to 30 parts by weight of modified glass fiber, 2 to 8 parts by weight of antistatic agent, 20 to 30 parts by weight of toughening agent, 2 to 8 parts by weight of stabilizer, and 0.5 to 3 parts by weight of processing flow aid.

[0036] In one embodiment, the antistatic agent (or long-lasting antistatic agent) includes carbon nanotubes (CNTs). Further, the antistatic agent may be carbon nanotubes, or it may be carbon nanotubes and conductive carbon black (e.g., superconducting carbon black).

[0037] In one embodiment, the particle size D50 of the carbon nanotubes used as long-lasting antistatic agents can be 15-50 μm, for example 20 μm, 25 μm, 30 μm, 35 μm, 40 μm or 45 μm; the diameter of the carbon nanotubes can be 2-10 nm, for example 3 nm, 5 nm or 8 nm; the aspect ratio (L / D) of the carbon nanotubes can be >1500, and further, L / D can be 1600-4000, for example 2000, 2500, 3000, 3500, 3800 or 3900.

[0038] In one embodiment, the specific surface area of ​​the conductive carbon black used as a long-lasting antistatic agent can be >700 m². 2 / g, with a particle size D50 of 20–50 nm.

[0039] In one embodiment, the toughening agent is chlorinated polyethylene (CPE) and / or methyl methacrylate-butadiene-styrene copolymer (MBS).

[0040] In one embodiment, the stabilizer is selected from one, two or more of metal soap stabilizers and thiol tin stabilizers, such as calcium zinc stabilizers.

[0041] In one embodiment, the processing flow aid (or processing aid) may be one or more of polyethylene wax, oxidized polyethylene wax, paraffin wax, monoglyceride, and dioctyl phthalate.

[0042] One embodiment of the present invention provides a polyvinyl chloride material, which is obtained by extruding the components of the above-mentioned polyvinyl chloride composition after mixing them.

[0043] In one embodiment, the components of a polyvinyl chloride composition are mixed and heated to 110–135°C (e.g., 120°C, 125°C, 130°C), and then cooled to 30–50°C (e.g., 35°C, 40°C, 45°C) to obtain a blended material; then, the blended material is extruded at 160–190°C (e.g., 165°C, 170°C, 175°C, 180°C, 185°C).

[0044] In one embodiment, the components of the polyvinyl chloride composition are added to a high-temperature mixer, the cutoff temperature of which is set to 110-135°C. The resulting mixture is then transferred to a low-temperature mixer, the cutoff temperature of which is set to 30-50°C, to obtain a blended material.

[0045] In one embodiment, the compounded materials are fed into a twin-screw extruder for extrusion processing. The twin-screw extruder has a screw length-to-diameter ratio of 36–50 (e.g., 40, 45), a temperature of 160–190°C (e.g., 170°C, 180°C), and a screw speed of 100–300 rpm (e.g., 150 rpm, 200 rpm, 250 rpm). Further, the extruded material can be air-cooled and pelletized.

[0046] One embodiment of the present invention provides an idler roller, including a roller body comprising or made of the aforementioned polyvinyl chloride material.

[0047] One embodiment of the present invention provides the use of the above-described modified glass fiber, the above-described polyvinyl chloride composition, or the above-described polyvinyl chloride material in the preparation of idler roller bodies.

[0048] In one embodiment of the present invention, glass fibers are modified by a tertiary amine silane coupling agent, which bonds tertiary amine groups to the surface of the glass fibers. Further, the modified glass fibers are reacted with polyvinyl chloride (PVC), where the tertiary amine functional groups form a temperature-controlled reversible cross-linking network with the active chlorine atoms (chlorine atoms bonded to allyl groups) of the PVC molecular chains. That is, at high temperatures (e.g., above 160°C), the reversible cross-linking network breaks down, allowing the PVC composition to be processed to obtain PVC material; at low temperatures (e.g., below 160°C), the tertiary amine groups on the surface of the modified glass fibers bond with the active chlorine of the PVC to form a cross-linking structure. Multiple PVC molecular chains are connected to the modified glass fibers through the aforementioned reversible cross-linking points, thereby forming a PVC material with a certain network structure. The modification reaction of the glass fibers with the tertiary amine silane coupling agent and the interaction between the modified glass fibers and PVC are as follows:

[0049]

[0050] One embodiment of the polyvinyl chloride (PVC) composition of the present invention, through modification of glass fibers with a tertiary amine silane coupling agent, enables the glass fibers to be linked to PVC, improving the interaction force between them. Simultaneously, the formation of a reversible network between the glass fibers and PVC restricts the high-temperature movement of PVC molecular chains, further improving the high-temperature creep resistance of PVC. Furthermore, the breaking temperature of the reversible crosslinking network is approximately 160°C, while the typical processing temperature of PVC is 165–190°C, at which temperature the crosslinking points break. Therefore, the reversible crosslinking points do not affect the processing performance of the matrix resin. After processing below 160°C, the reversible crosslinking points automatically form. Through the action of these reversible crosslinking points, the interaction between the glass fibers and PVC is enhanced, restricting the movement of PVC molecular chains at high temperatures and improving the high-temperature creep resistance of the material.

[0051] The polyvinyl chloride material of one embodiment of the present invention has high temperature creep resistance and flame retardant and antistatic properties.

[0052] The polyvinyl chloride composition of one embodiment of the present invention uses carbon nanotubes with a high aspect ratio as an antistatic agent, which not only plays an antistatic role, but also plays a certain synergistic role in the high temperature creep resistance of the material.

[0053] The preparation and application of a polyvinyl chloride material according to one embodiment of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. The test methods involved in each embodiment and comparative example are as follows.

[0054] 1. HDT load deformation temperature test

[0055] According to GB / T 1634, the heat load deformation temperature of the material is tested using Method A with a bending stress of 1.80 MPa.

[0056] 2. Vicat softening temperature test

[0057] According to GB / T 1633, the Vicat softening temperature of the test material is determined using A. 50 Method: Use a force of 10N and a heating rate of 50℃ / h.

[0058] 3. High-temperature creep resistance test

[0059] The high-temperature creep characteristics of PVC material were tested under stress of 5 MPa and temperature of 50 °C, and the creep deformation-time curve was recorded.

[0060] 4. Testing of Young's modulus and elongation at break

[0061] The sample was pressed into a 4 mm thick sample at 175℃ and 150 bar pressure, and then tensile properties were tested according to GB / T1040.2 at a tensile rate of 50 mm / min to obtain the Young's modulus and elongation at break of the sample.

[0062] 5. Surface resistivity test

[0063] The sample was pressed into a 5mm thick sample at 175℃ and 150bar pressure, and then the surface resistance of the sample at 23℃ and 65% relative humidity was tested according to the MT113 standard.

[0064] 6. Flame retardancy rating test

[0065] The sample was compressed into a 3mm thick sample at 175℃ and 150bar pressure, and then cut into test strips with a length of 125mm, a width of 13mm, and a thickness of 3mm. According to the UL94 test standard, the sample was placed at 23℃ and 50% relative humidity for 48 hours, and then the flammability rating of the sample was tested according to the UL-94V-0 standard.

[0066] Example 1

[0067] Preparation of modified glass fibers

[0068] Add 50g of N,N-dimethyl-3-aminopropyltrimethoxysilane to 2000g of deionized water, adjust the pH of the solution to 4 with glacial acetic acid, and hydrolyze at 50℃ for 0.5h; then add 1000g of glass fiber (TCR438G-13-4.5, fiber diameter 13um, length 4.5mm) to the solution, and continue to stir the reaction at 50℃ for 0.5h; finally, heat and vacuum dry the system to obtain glass fiber modified with tertiary amine silane coupling agent (referred to as "modified glass fiber 1").

[0069] Preparation of polyvinyl chloride materials

[0070] S1: Weigh 100g of type 5 PVC, 10g of the above-mentioned modified glass fiber, 5g of carbon nanotubes (L / D=4000), 5g of calcium-zinc stabilizer (Chengdu Maike Polymer MK-6019), 20g of chlorinated polyethylene toughening agent (CPE-135A), and 2g of processing aids (1g of oxidized polyethylene wax AC316 and 1g of polyethylene wax CHF210). Add them to a high-temperature mixer and mix to 125°C. Then transfer the material to a low-temperature mixer and cool it to 40°C.

[0071] S2: The cooled material from step S1 is extruded using a twin-screw extruder with a length-to-diameter ratio of 40. The temperature of the twin-screw extruder is 180°C, the screw speed is 180 rpm, and the material is air-cooled and pelletized to obtain a high-temperature resistant and antistatic polyvinyl chloride material.

[0072] Example 2

[0073] This embodiment uses the same raw materials and processes as Example 1 to prepare polyvinyl chloride material, the only difference being that in step S1, the amount of modified glass fiber 1 is 20g and the amount of chlorinated polyethylene toughening agent is 25g.

[0074] Example 3

[0075] This embodiment uses the same raw materials and processes as Example 1 to prepare polyvinyl chloride material, the only difference being that in step S1, the amount of modified glass fiber 1 is 30g and the amount of chlorinated polyethylene toughening agent is 30g.

[0076] Example 4

[0077] Preparation of modified glass fibers

[0078] Add 50g of N-(3-dimethylethyl)-3-aminopropylmethyldimethoxysilane to 2000g of deionized water, adjust the pH of the solution to 4 with glacial acetic acid, and hydrolyze at 50℃ for 0.5h; then add 1000g of glass fiber (model 101C-10-13, fiber diameter 10um, length 13mm) to the solution, and continue to stir the reaction at 50℃ for 0.5h; finally, heat and vacuum dry the system to obtain glass fiber modified with tertiary amine silane coupling agent (referred to as "modified glass fiber 2").

[0079] Preparation of polyvinyl chloride materials

[0080] S1: Weigh 100g of type 5 PVC, 10g of the above-mentioned modified glass fiber, 5g of carbon nanotubes (L / D=4000), 5g of calcium-zinc stabilizer, 20g of chlorinated polyethylene toughening agent, and 2g of processing aids (1g of oxidized wax and 1g of polyethylene wax) and add them to a high-temperature mixer to mix to 125°C. Then transfer the material to a low-temperature mixer to cool the material to 40°C.

[0081] S2: The cooled material from step S1 is extruded using a twin-screw extruder with a length-to-diameter ratio of 40. The temperature of the twin-screw extruder is 180°C, the screw speed is 180 rpm, and the material is air-cooled and pelletized to obtain a high-temperature resistant and antistatic polyvinyl chloride material.

[0082] Example 5

[0083] This embodiment uses essentially the same raw materials and processes as Example 4 to prepare polyvinyl chloride material, the only difference being that in the preparation of modified glass fiber, 3-piperazinylpropylmethyldimethoxysilane is used instead of N-(3-dimethylethyl)-3-aminopropylmethyldimethoxysilane, and the amount of 3-piperazinylpropylmethyldimethoxysilane used is 10g, to obtain glass fiber modified with tertiary amine silane coupling agent (referred to as "modified glass fiber 3").

[0084] Example 6

[0085] This embodiment uses essentially the same raw materials and processes as Example 1 to prepare polyvinyl chloride materials, with the only difference being that in the preparation of modified glass fiber, N-(piperazinylethyl)-3-aminopropylmethyldimethoxysilane is used instead of N,N-dimethyl-3-aminopropyltrimethoxysilane, and the amount of N-(piperazinylethyl)-3-aminopropylmethyldimethoxysilane used is 100g, resulting in glass fiber modified with tertiary amine silane coupling agent (referred to as "modified glass fiber 4").

[0086] Comparative Example 1

[0087] This example uses essentially the same raw materials and processes as Example 1 to prepare polyvinyl chloride material. The only difference is that in step S1, modified glass fiber is not used, and 8g of conductive carbon black is used instead of 5g of carbon nanotubes as an antistatic agent. The amount of chlorinated polyethylene toughening agent used is 25g.

[0088] Comparative Example 2

[0089] This example uses essentially the same raw materials and processes as Example 1 to prepare polyvinyl chloride material, with the only difference being that in step S1, 10g of glass fiber is used instead of modified glass fiber, 8g of conductive carbon black is used instead of 5g of carbon nanotubes as an antistatic agent, and the amount of chlorinated polyethylene toughening agent is 25g.

[0090] Comparative Example 3

[0091] This example uses essentially the same raw materials and processes as Example 1 to prepare polyvinyl chloride materials, the only difference being that in the preparation of modified glass fiber, KH550 is used instead of the tertiary amine silane coupling agent to obtain modified glass fiber 5.

[0092] Comparative Example 4

[0093] This example uses essentially the same raw materials and processes as Comparative Example 3 to prepare polyvinyl chloride materials, with the only difference being that in step S1, 5g of conductive carbon black is used instead of 5g of carbon nanotubes as an antistatic agent.

[0094] The raw material components and amounts for each embodiment and comparative example are shown in Table 1. The polyvinyl chloride materials prepared according to the aforementioned method were subjected to relevant performance tests, and the results are shown in Table 2.

[0095] Table 1

[0096]

[0097]

[0098] Table 2

[0099]

[0100] Referring to Example 1, Comparative Example 3, and Table 1, the only difference between Example 1 and Comparative Example 3 is the type of silane coupling agent used in the modified glass fiber. Example 1 uses a tertiary amine silane coupling agent to modify the glass fiber, while Comparative Example 3 uses KH550 (γ-aminopropyltriethoxysilane) to modify the glass fiber. Further referring to Table 2, it can be seen that the Vicat softening temperature and HDT load deformation temperature of the polyvinyl chloride material in Example 1 are higher than those in Comparative Example 3, while the creep is lower. Furthermore, the elongation at break of the polyvinyl chloride material in Example 1 is significantly higher than that in Comparative Example 3, and the surface resistivity is significantly lower than that in Comparative Example 3. See also... Figure 1 It can be seen that the deformation of Comparative Example 3 continuously increases with the extension of time, indicating that its material has poor creep resistance. In contrast, the deformation of Example 1, after reaching an initial strain, shows relatively small elongation as creep time continues to increase, indicating that the material has better deformation resistance and creep resistance. Therefore, the embodiments of the present invention, by modifying glass fiber with a tertiary amine silane coupling agent and using it to prepare polyvinyl chloride material, can simultaneously improve the high-temperature creep resistance, antistatic properties, and mechanical properties of the material compared to using a primary amine silane coupling agent.

[0101] Furthermore, referring to Comparative Examples 3 and 4 and Table 1, it can be seen that the only difference between Comparative Examples 3 and 4 is that Comparative Example 3 uses carbon nanotubes as the antistatic agent, while Comparative Example 4 uses conductive carbon black as the antistatic agent. Further referring to Table 2, it can be seen that the surface resistance of the polyvinyl chloride material in Comparative Example 3 is much lower than that in Comparative Example 4. Therefore, one embodiment of the present invention can greatly improve the antistatic properties of polyvinyl chloride materials by using carbon nanotubes as the antistatic agent.

[0102] Unless otherwise specified, the terms used in this invention have the meanings commonly understood by those skilled in the art.

[0103] The embodiments described in this invention are for illustrative purposes only and are not intended to limit the scope of protection of this invention. Those skilled in the art can make various other substitutions, changes and improvements within the scope of this invention. Therefore, this invention is not limited to the above embodiments, but is only defined by the claims.

Claims

1. A polyvinyl chloride composition comprising polyvinyl chloride and an additive, said additive comprising modified glass fiber; wherein, The modified glass fiber is prepared by reacting a tertiary amine silane coupling agent with the glass fiber.

2. The composition according to claim 1, wherein, The tertiary amine silane coupling agent includes one or more of the following compounds: R1, R2, R4, and R5 are each independently selected from alkyl groups containing 1 to 3 carbon atoms; R3 is selected from alkyl groups or alkoxy groups containing 1 to 3 carbon atoms. a and b can be 1, 2, 3 or 4 independently.

3. The composition according to claim 1, wherein, R1, R2, R4, and R5 are each independently methyl or ethyl, R3 is methyl, ethyl, methoxy, or ethoxy, a is 2 or 3, b is 2 or 3; and / or, The mass ratio of the glass fiber to the tertiary amine silane coupling agent is 100:0.2-10.

4. The composition according to claim 1, wherein, The tertiary aminosilane coupling agent includes 3-piperazinylpropylmethyldimethoxysilane, 3-piperazinylpropyltrimethoxysilane, N-(piperazinylethyl)-3-aminopropylmethyldimethoxysilane, and N-(piperazinylethyl)-3-aminopropyltrimethoxysilane. One or more of the following: N-(3-dimethylethyl)-3-aminopropylmethyldimethoxysilane, N-(3-dimethylethyl)-3-aminopropyltrimethoxysilane, N-dimethylaminopropyl-aminopropylmethyldimethoxysilane, N-dimethylaminopropyl-aminopropyltrimethoxysilane, N-(2-dimethylaminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-dimethylaminoethyl)-3-aminopropyltrimethoxysilane, N,N-diethyl-3-aminopropyltrimethoxysilane, and N,N-dimethyl-3-aminopropyltrimethoxysilane.

5. The composition according to claim 1, wherein, The glass fibers have a diameter of 5–20 μm and a length of 4–40 mm; and / or, The mass ratio of the polyvinyl chloride to the modified glass fiber is 100:5 to 40; and / or, The additives include one or more of antistatic agents, toughening agents, stabilizers, and processing flow aids; and / or, The method for preparing the modified glass fiber includes: hydrolyzing a tertiary amine silane coupling agent under conditions of pH 2 to 6, and then adding glass fiber to carry out the reaction.

6. The composition according to claim 5, comprising 100 parts by weight of polyvinyl chloride, 5 to 40 parts by weight of the modified glass fiber, 2 to 15 parts by weight of the antistatic agent, 5 to 30 parts by weight of the toughening agent, 2 to 10 parts by weight of the stabilizer, and 0.5 to 4 parts by weight of the processing flow aid; and / or, The antistatic agent includes a long-acting antistatic agent; and / or, The antistatic agent comprises carbon nanotubes or comprises carbon nanotubes and conductive carbon black; and / or, The toughening agent is chlorinated polyethylene and / or methyl methacrylate-butadiene-styrene copolymer; and / or, The stabilizer is selected from one or more of metal soap stabilizers and tin thiols stabilizers; and / or, The processing flow aid includes one or more of polyethylene wax, oxidized polyethylene wax, paraffin wax, monoglycerides, and dioctyl phthalate; and / or, The hydrolysis reaction and the reaction after adding the glass fiber were both carried out at 30–70°C.

7. A polyvinyl chloride material, obtained by extruding the components of the polyvinyl chloride composition according to any one of claims 1 to 6.

8. A roller comprising a roller body, the roller body comprising the polyvinyl chloride material of claim 7.

9. A modified glass fiber, prepared by reacting a tertiary amine silane coupling agent with the glass fiber.

10. The use of the polyvinyl chloride composition of any one of claims 1 to 6, the polyvinyl chloride material of claim 7, or the modified glass fiber of claim 9 in the preparation of idler roller bodies.